Trzeci sektor w Unii Europejskiej - Kamiński, Stanisław (The Third Sector in the European Union, 2007)
The aim of the article is to present the history of European Union policy towards non-governmental organizations. The author analyzes official European documents and comes to conclusion that the role of the third sector was not recognized until 1984. Since then there was more and more emphasis put on the co-operation between public and non-governmental. Another important conclusion is the fact that there are numerous differences among member states as far as law and economic regulations are concerned. The last part of the article includes some data on the European non-governmental organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 53-59